Comparison of two maneuvers to identify Carnett's sign in patients with chronic abdominal pain. Randomized controlled clinical trial - Otero Regino, William (2025)
Introduction: Chronic abdominal pain (CAP) is a challenge in daily consultation. The most frequent cause is anterior cutaneous nerve entrapment syndrome (ACNES), which is diagnosed when the Carnett sign is positive. There are two ways to identify the Carnett sign: elevating the head and trunk or elevating the lower extremities. To date, these two ways of looking for the Carnett sign have not been compared. Objective: To compare the effectiveness of the two maneuvers to identify the Carnett sign, evaluate the effectiveness of infiltration of the tender points with 2% lidocaine, and estimate the cost of examinations before diagnosis. Material and methods: Randomized controlled study. Results: 1320 patients were included and 660 patients were randomly assigned to group A: elevation of the head and trunk and 660 to group B: elevation of the lower extremities. Both maneuvers were similarly effective in identifying the Carnett sign. Infiltration of the points produced immediate relief in most patients. The costs of different studies before definitive diagnosis were approximately US$ 861 000 (dollars) versus US$ 66.00, which would be equivalent to 7.6% of the expenses incurred for tests performed before diagnosis. Conclusion: The two ways of exploring the Carnett sign have similar efficacy. Infiltration with 2% lidocaine produced rapid and significant improvement of pain with minimal side effects. Not knowing the Carnett sign increases health costs.